2021
DOI: 10.1007/jhep09(2021)012
|View full text |Cite
|
Sign up to set email alerts
|

The Abrikosov vortex in curved space

Abstract: We study the self-gravitating Abrikosov vortex in curved space with and with-out a (negative) cosmological constant, considering both singular and non-singular solutions with an eye to hairy black holes. In the asymptotically flat case, we find that non-singular vortices round off the singularity of the point particle’s metric in 3 dimensions, whereas singular solutions consist of vortices holding a conical singularity at their core. There are no black hole vortex solutions. In the asymptotically AdS case, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Later, work was then extended to include singular vortex solutions besides non-singular ones [4]. Vortices with conical singularities were obtained in flat backgrounds and BTZ black hole solutions were obtained in curved backgrounds, though it was found that the vortex cannot ultimately hold a black hole at its core [4]. Our present paper introduces the non-minimal coupling term which is missing in all previous studies of gravitating vortices.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Later, work was then extended to include singular vortex solutions besides non-singular ones [4]. Vortices with conical singularities were obtained in flat backgrounds and BTZ black hole solutions were obtained in curved backgrounds, though it was found that the vortex cannot ultimately hold a black hole at its core [4]. Our present paper introduces the non-minimal coupling term which is missing in all previous studies of gravitating vortices.…”
Section: Introductionmentioning
confidence: 90%
“…We work in natural units where = c = 1. Though our parameters and quantities such as the radius, mass and magnetic field are quoted as numbers, they should be thought of as having a unit attached to them (except for the winding number n which is a pure number) 4 . As we have seen, a negative Λ automatically ensures that the asymptotic cosmological constant Λ ef f will be negative.…”
Section: Plot Of Vortex Profiles and Magnetic Field In Ads 3 For Diff...mentioning
confidence: 99%
See 3 more Smart Citations